Transport models for predicting spontaneous ignition of pressurized hydrogen released into a tube - Gang Luo; Wenping Zhang; Zixuan Yang; Lijing Zhang; Jinfeng Zhang (Case Studies in Thermal Engineering, 2025)
Spontaneous ignition presents a significant hazard in high-pressure hydrogen storage and transportation. However, fundamental processes governing spontaneous ignition at the microscopic scale, such as transport models and ignition initiation, are not fully explained. In this paper, OpenFOAM is employed to study three different transport models for predicting spontaneous ignition of pressurized hydrogen released into a tube. The validity of the present numerical system is confirmed by comparing the numerical and experimental pressure. The results show that transport models have significant impacts on spontaneous ignition. The simulation discover two different ignition modes brought by the different transport models and the flame quenching in the tube. The transport model has been demonstrated to significantly influence the mixing of hydrogen and oxygen within the boundary layer, as well as ignition and flame development: viscous transport models can assist in the hydrogen-oxygen mixing at the boundary layer and reduce the critical burst pressure. In contrast, the inviscid transport model can generate more intense turbulence and multiple mushroom-shaped flames under the influence of Rayleigh-Taylor instability.